Evaluation of the Higher Modes of Vibration on Rigid Response Coefficient and Earthquake Resistance Design of Structures: Investigating the Impact of Earthquake on Structures and Evaluating Rigid Response Coefficient (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The effect of the earthquake on a structure depends not only on the peak value of groundacceleration, but also on the size and shape of the building, the arrangement of structural elements, andthe presence of mass and stiffness irregularities. Basic modes in irregular structures are often isolatedand may not affect the response of other areas of the structure in any significant way. Straight-line fit tosemi logarithmic graphs between key frequency f1 rigid frequency independent of damping are used toderive the empirical expressions for rigid response coefficient. As the study's findings demonstrate, thefundamental mode approach for regular structures 90 modal mass criteria for the number of modesto be included for dynamic analysis of irregular structures are insufficient. Shear forces areunderestimated at the top and bottom levels in numerical instances when the current criterion is used.Elastic seismic analysis of irregular structures can be simplified by the residual mode's ability tosimulate dampened periodic response.A tool MathCAD is used for developing different mathematical models for dynamic analysis and tocalculate section capacity of RC and steel sections as per IS Codes.Further software STAAD.Pro and ETABS is used for modelling and dynamic analysis of real-lifestructures. The output of both the models is used to verify and validate output and correctness of eachother